Bright Organic Mechanoluminescence and Remarkable Mechanofluorochromism from Circularly Polarized TADF Enantiomers with Aggregation‐Induced Emission Properties. Issue 5 (8th December 2022) - Zheng, Yitao; Zhang, Letian; Huang, Zihao; Li, Shufeng; Zuo, Lingqi; Liang, Yaohui; Liu, Cong; Luo, Suilian; Shi, Guang; Zhao, Zujin; Sun, Fengqiang; Xu, Bingjia
Abstract: The development of circularly polarized thermally activated delayed fluorescence (CP‐TADF) luminogens with stimuli‐response characteristics remains challenging. Herein, a pair of organic enantiomers, S ‐CzTA and R ‐CzTA, with aggregation‐induced emission properties, have been successfully developed by introducing chiral 1, 2, 3, 4‐tetrahydronaphthalene and carbazole to phthalimide. They present CP‐TADF properties in toluene solutions, giving dissymmetric factors of 0.84×10 −3 and −1.03×10 −3, respectively. In the crystalline state, both S ‐CzTA and R ‐CzTA can emit intense blue TADF and produce very bright sky‐blue mechanoluminescence (ML) and remarkable mechanofluorochromism (MFC) under the stimuli of mechanical force. Single‐crystal analysis and theoretical calculation results suggest that their ML activities are probably associated with their chiral and polar molecular structures and unique non‐centrosymmetric molecular packing modes. Furthermore, the MFC properties of the enantiomers likely originate from the destruction of crystal structure, leading to the planarization of molecular conformation. This work may provide helpful guidance for developing new CP‐TADF materials with force‐stimuli‐responsive properties. Abstract : A pair of organic enantiomers with aggregation‐induced emission and circularly polarized thermally activated delayed fluorescence properties have been developed successfully. Furthermore, it is found that their crystals can emit strong blue thermally activated delayed fluorescence and produce bright sky‐blue mechanoluminescence and remarkable mechanofluorochromism under the stimuli of force.